Direct Expansion of Chondrocytes in a Dynamic Three-Dimensional Culture System: Overcoming Dedifferentiation Effects in Monolayer Culture - Gharravi, Anneh Mohammad; Orazizadeh, Mahmoud; Hashemitabar, Mahmoud (Artificial organs, 2014)
Maintenance of the chondrocyte phenotype during cell culture to successful transplantation of cartilage is highly challenging. However, the question of the optimal method of isolation and expansion of chondrocytes for tissue engineering has not previously been investigated in detail. The present study investigates the possibility of improved in vitro maturation of chondrocytes through a method of cell duplication that does not subject chondrocytes to dedifferentiation. The culture chamber of the bioreactor was designed with an internal geometry that mimicked that of a ball‐and‐socket joint. The shear stresses exerted on the surface of the bioreactor chamber wall by a peristaltic pump operating at flow rates of 2 mL/min were simulated by computational fluid dynamics (CFD) modeling. Small pieces (5 mm) of calf nasal septum cartilage were prepared and exposed to trypsin and 0.2% collagenase type II in Dulbecco's modified Eagle's medium (DMEM), which was then replaced with unsupplemented DMEM. The cells were harvested and then immediately seeded into alginate scaffolds. All cell‐seeded scaffolds were cultured for 3–5 days in flasks, then transferred to the bioreactor and dynamically cultured for 3–5 days under direct perfusion with 2 mL/min DMEM. After culture in the bioreactor, all cell‐seeded scaffolds were fixed in Bouin fixative, dehydrated, cleared, and then embedded in paraffin wax. Sections of 5–7 μm were cut and stained with several histochemical staining methods. The results of CFD modeling indicated peak velocity and maximum wall shear stress were 3.406 × 10−3 m/s and 0.0482 dyn/cm2 (1 Pa = 10 dyn/cm2), respectively. Histological examination of chondrocytes cultured in the bioreactor revealed evidence of cartilage‐like tissue with lacuna and chondron formation. The cartilage‐like matrix had accumulated within the lumen of clusters of round mature chondrocytes, with the cells surrounding the metachromatic territorial matrix‐staining strongly with toluidine blue. Sections stained with the hematoxylin/safranin O/fast green and Alcian blue/nuclear fast red methods show sulfated glycosaminoglycans in the matrix (produced by the chondrocytes) as intense red and blue, respectively. The findings of the present study indicate that incubation in DMEM supplemented with enzymes followed by explant isolation and culture in a bioreactor is the optimal method for the direct expansion of chondrocytes for cartilage tissue engineering.